France : Financial Sector Assessment Program-Technical Note-Anti-Money Laundering and Combating the Financing of Terrorism Regime in France. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) regime in France summarizes the findings of a targeted review of France's AML/CFT framework with respect to measures to prevent and combat terrorist financing (TF), risk-based supervision of banks, real estate agents, company service providers and lawyers, measures to tackle cross-border crimes, and fintech. It provides a factual update on the key measures taken by the authorities since France's previous assessment. Authorities are recommended to promote stronger AML/CFT controls by enhancing supervision of lawyers and the real estate sector and providing more guidance on cross-border money laundering threats. French banks are employing increasingly sophisticated tools, including machine learning, to carry out their due diligence obligations with respect to TF. More systematic guidance on TF-related indicators and timely feedback may help banks' detection of potential of TF and to reduce risks of financial exclusion.